Interactive design modeling of 3D styling combining Bezier curve and Harris corner point detection algorithm - Hua Song; Ziqiao Wen (PLoS ONE, 2025)
Enhancing the effectiveness and precision of 3D modeling design has become the main focus of current research due to the ongoing development of 3D modeling applications in numerous fields. In this study, an interactive 3D modeling design model based on Bezier curve and Harris corner detection algorithm is constructed. First, the output image is denoised, and then the improved Harris corner detection algorithm is used to obtain the feature points, which ensures the clarity of the image while extracting the key features. Second, a new sketch contour generation method is proposed by combining feature points with Bezier curves. Finally, a combination of Bezier surfaces and Delaunay triangulation is used for surface reconstruction and 3D modeling of the image is rendered. The results revealed that the improved Harris corner point detection algorithm could detect 120 3D image features of a kettle in 3.2s, and detect 50 3D image feature points of a vase in only 0.43s, which had very high detection speed and accuracy. The total time for surface reconstruction of a mechanical part model by combining Bezier surface and Delaunay triangulation was 0.524s, which met the basic user requirements. The teapot image modeling experiment proves the feasibility of the overall design method of the study. Moreover, through the 3D modeling interaction design model designed by the study, the designer can construct the accurate 3D modeling based on the real thing faster, which greatly saves time, improves efficiency, and pushes forward the development of 3D modeling design technology.